Prakashachi Savali - Joshi, Dinkar; Bhagwat, Smita (Pune: Mehta Publishing Books, 2022)
Life of harilal gandhi, the eldest son of mahatma gandhi. Bapu had failed to convince two people in his lifetime, one was jinnah and the other was harilal. This novel was simultaneously serialized in the sunday supplements of three gujarati dailies: sam kaleen of bombay, jansatta of ahmedabad and loksatta of vadodra. In this book the author tries to make an ardent effort to understand yet another enigmatic facet of human life. The tussle between the father and the son was the most poignant and pathetic story of their lives. When gandhi, who was busy attending meetings and conferences where the fate of forty crore indians was to be decided often found headline in a newspaper screaming -police arrested drunk harilal for creating a scene on the road and sometimes harilal himself from the dais of the fundamentalist muslim organizations meeting -i shall continue fighting till ba and bapu embrace islam.
Keywords: Mahatma Gandhi; Harilal Gandhi; Religious transformation; Ideological conflict